If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(3 + 1) = -10(x + -4) + -14x Combine like terms: 3 + 1 = 4 -4(4) = -10(x + -4) + -14x Multiply -4 * 4 -16 = -10(x + -4) + -14x Reorder the terms: -16 = -10(-4 + x) + -14x -16 = (-4 * -10 + x * -10) + -14x -16 = (40 + -10x) + -14x Combine like terms: -10x + -14x = -24x -16 = 40 + -24x Solving -16 = 40 + -24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24x' to each side of the equation. -16 + 24x = 40 + -24x + 24x Combine like terms: -24x + 24x = 0 -16 + 24x = 40 + 0 -16 + 24x = 40 Add '16' to each side of the equation. -16 + 16 + 24x = 40 + 16 Combine like terms: -16 + 16 = 0 0 + 24x = 40 + 16 24x = 40 + 16 Combine like terms: 40 + 16 = 56 24x = 56 Divide each side by '24'. x = 2.333333333 Simplifying x = 2.333333333
| 7/9=r/2 | | 3w^2-(w-5)(w-3)=2w^2+1 | | 40.5+X=96.3 | | 2y=18y+64 | | 8a-a-2=12 | | -7/2(y-8)-1/4 | | 2r-3.1=1.6 | | 25000-4x=0 | | 2y-4=18y+64 | | y-5+6= | | .25x+7=x-8 | | 0=-4w+4 | | 6w-5=1w | | .66x+.33=-1.33 | | P-0.15p=29.74 | | 10=5t+16 | | 18-2x=-8(-5+3) | | 1+3(b-8)=-35-b | | -2w-14=-4 | | x+(.40x)=168 | | 2x-6=4x+7 | | 5=r-7 | | -4-7p=-4(p-2) | | -8(5h+9)=-34 | | 5-2x-4=15 | | 40.5+96.3+X=180 | | -16+8x=14x+10x | | 6v=7.68 | | 8(8+8r)=-7-7r | | 6+12x+3x^2=0 | | 4.8=3w | | 8(x+6)+8(x+6)=7x-7 |